2018
DOI: 10.1083/jcb.201711022
|View full text |Cite
|
Sign up to set email alerts
|

Processive flow by biased polymerization mediates the slow axonal transport of actin

Abstract: Classic pulse-chase studies have shown that actin is conveyed in slow axonal transport, but the mechanistic basis for this movement is unknown. Recently, we reported that axonal actin was surprisingly dynamic, with focal assembly/disassembly events (“actin hotspots”) and elongating polymers along the axon shaft (“actin trails”). Using a combination of live imaging, superresolution microscopy, and modeling, in this study, we explore how these dynamic structures can lead to processive transport of actin. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 70 publications
1
29
1
Order By: Relevance
“…Farina et al [6] described that centrosomal F-actin polymerization is Arp2/3 dependent. In contrast, we found that formins but not Arp2/3 contribute to the somatic F-actin organization in neurons, as shown for axonal Factin organization of mature neurons [42,43]. Furthermore, a novel actin network was described, which mediates long-range vesicle transport and asymmetric oocyte division [46,47].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Farina et al [6] described that centrosomal F-actin polymerization is Arp2/3 dependent. In contrast, we found that formins but not Arp2/3 contribute to the somatic F-actin organization in neurons, as shown for axonal Factin organization of mature neurons [42,43]. Furthermore, a novel actin network was described, which mediates long-range vesicle transport and asymmetric oocyte division [46,47].…”
Section: Discussionmentioning
confidence: 63%
“…It was previously shown that axons of mature neurons contain F‐actin “hotspots” which are the source of dynamic actin trails . Importantly, Ganguly et al showed that the activity of axonal F‐actin “hotspots” correlates with stationary endosomes and are Formins‐dependent.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, an anterograde F-actin flow was described during neuronal migration (He, Zhang, Guan, Xia, & Yuan, 2010;Solecki et al, 2009) and at the base of the growth cones (Burnette et al, 2008). Importantly, using high-resolution microscopy techniques, it was demonstrated that mature axonal shafts contain actin "hotspots" and "trails," which contribute to axon anterograde actin transport (Chakrabarty et al, 2019;Ganguly et al, 2015). Altogether, these studies suggest a strong centrifugal component to the neuronal F-actin organization, in addition to the existing local assembly of filaments of F-actin in the growth cones.…”
Section: Centrosome As An F-actin Organization Center During Early mentioning
confidence: 99%
“…We have been using STORM since 2013, then DNA-PAINT to study the organization of the axonal cytoskeleton Papandréou and Leterrier, 2018), resolving the architecture of axonal actin and spectrins (Ganguly et al, 2015;C. Y.-M. Huang et al, 2017;Leterrier et al, 2015) as well as the mechanisms of slow axonal transport (Chakrabarty et al, 2019;Ganguly et al, 2017). We have also helped developing SMLM imaging modalities and analysis strategies (Culley et al, 2018;Laine et al, 2019).…”
Section: Introductionmentioning
confidence: 99%